Kidney function assessment and endpoint ascertainment in clinical trials. (30th December 2021) - Khan, Muhammad Shahzeb; Bakris, George L; Packer, Milton; Shahid, Izza; Anker, Stefan D; Fonarow, Gregg C; Wanner, Christoph; Weir, Matthew R; Zannad, Faiez; Butler, Javed
Abstract: Heterogeneity in the reporting of kidney function, kidney outcomes, and definitions for kidney endpoints in clinical trials makes it challenging to compare results and gauge incremental benefit of interventions across trials. We conducted a systematic review of the ascertainment of baseline kidney variables, reporting of kidney endpoints, and definitions used to characterize these endpoints in type 2 diabetes mellitus (T2DM), kidney, and heart failure (HF) trials. Medline, Scopus, and ClinicalTrials.gov were searched from January 2014 through January 2021 for large (>1000 participants) T2DM, HF, and kidney disease trials and their secondary analyses. Trial publication and supplementary appendices were searched to abstract relevant data. Thirty-three trials (16 T2DM; 10 HF; 7 kidney diseases) were included. Thirteen trials did not include patients with estimated glomerular filtration rate (eGFR) <30 mL/min/1.73 m 2 and for trials that did, representation of this cohort ranged from 0.1% to 15%. Reporting of baseline kidney function and albuminuria remained low, especially in HF trials. Variability was observed in the definition of chronic kidney disease, sustained decline in eGFR, end-stage kidney disease, kidney death, and kidney composite endpoint across trials. eGFR slope was reported in less than half trials, with differences observed in statistical models, definition of acute or chronic slope, and follow-up duration across trials. Significant heterogeneity in reporting of kidney function and kidney outcomes in large T2DM, kidney, and HF trials underscores the need for future stakeholders to draft a consensus solution. Detailed profiling of patients at baseline, accrual of more patients with advanced kidney disease, and standardization of definitions in trials may improve the ability to compare the results across trials. Graphical Abstract: